Surgical Management of Aural Haematoma Resultant of Tick Infestation in a Non-descript Sheep – A Case Report - Lamani, Thara Singh D.; Kamalakar, G.; Sunil, C. L.; Murthy , K. M. Srinivasa; Nagaraja, B. N. (International Journal of Livestock Research, 2019)
An adult non-descript sheep was brought to the clinic with complaint of swollen right ear pinna since 10 days. On physical examination, soft fluctuating swelling covering entire medial aspect of right ear was noticed. Few ticks were found over body and ears. It was diagnosed as aural haematoma upon needle aspiration and was surgically drained out by a linear incision under xylazine sedation and auriculo-palpebral nerve block. Parallel to the line of incision, series of through and through interrupted horizontal mattress sutures were placed and protective overhead pressure bandage applied. Sutures were removed after 15 days and the animal showed uneventful recovery.